Psychological perspectives in the study of authoritarianism - Etchezahar, Edgardo Daniel (2013)
Different theoretical perspectives have been developed within the psychology framework for the analysis of the authoritarian phenomenon. They constituted some of the background lines of what would after wards be considered as the field of Political Psychology. The first approach takes place in the late nineteenth and early twentieth century`s, along with group psychology, where authoritarianism is studied as an emergent behavior of crowds. Subsequently, developments inauthoritarian personality suggest a change in the analysis axes by studying the phenomenon in an intra-individual way. A third perspective arises with the cognitive approach, represented by the concept of dogmatism, which emphasized the study of beliefs and the way in which individuals defend them. Parallel to this approach, advances in the field of Experimental Psychology on obedience, account for the situation in the authoritarian phenomenon. Later on, the study of authoritarian personality is taken up once more with the concept of right-wing authoritarianism, which is defined as the individual differences in the covariation of three attitudinal clusters (authoritarian submission, authoritarian aggression and conventionalism). Finally, the most recent perspective for the study of the phenomenon suggests rethinking rightwing authoritarianism as an intergroup phenomenon, since its three attitudinal clusters account for a group phenomenon, plus a personality trait. The main objective of this paper is to critically review each of the six perspectives which have approached the study of authoritarianism as psycho-political phenomena, showing its peculiarities as well as its differences so as to finally consider which of those are still acceptable alternatives for the interpretation of this phenomenon.